Alternative pathways for hydrogen disposal during fermentation in the human colon. Issue 6 (June 1990) - Gibson, G R; Cummings, J H; Macfarlane, G T; Allison, C; Segal, I; Vorster, H H; Walker, A R
Abstract : Hydrogen gas, which is produced during fermentation in the human colon, is either excreted in breath or metabolised by gut bacteria through a variety of pathways. These may include methanogenesis, dissimilatory sulphate reduction, and acetogenesis. To determine which of these routes predominates in the large intestine, stools were taken from 30 healthy subjects and incubated as 5% (w/v) slurries with Lintner's starch. In 23 of 30 subjects, methane production was the main method of hydrogen disposal. In the remaining seven, high rates of sulphate reduction were recorded together with raised production of H2S. All samples showed relatively low rates of hydrogen evolution and of acetate formation from CO2 and H2. Sulphate reduction and methanogenesis seem to be mutually exclusive in the colon and this is probably linked to sulphate availability. Sulphate reduction, methanogenesis, and acetogenesis were strongly influenced by pH. Sulphate reduction was optimal at alkaline pH values whereas methane production was maximal at a neutral pH and acetogenesis favoured acidic conditions. Faecal H2S values were related to carriage of sulphate reducing bacteria. These data show that a number of competing pathways for hydrogen disposal are possible in the large gut and that a variety of factors such as colonic pH and sulphate availability can determine which of these mechanisms predominates.